Experiment with movement - Murphy, Bryan (Minneapolis, Minn. : Lerner Publications, 1991)
Presents simple experiments demonstrating the basic scientific principles of movement.
"First published in 1991 by: Two-Can Publishing Ltd. ... London--T.p. verso.
Includes index.
School Library Journal.
4.9.
4.9
3-6
Keywords: Force and energy -- Experiments -- Juvenile literature; Motion -- Experiments -- Juvenile literature; Experiments; Force and energy -- Experiments; Motion -- Experiments; Force and energy -- Experiments; Motion -- Experiments; Science -- Experiments